Socio-hydrological modelling of flood-risk dynamics: comparing the resilience of green and technological systems. Issue 6 (26th April 2017) - Ciullo, Alessio; Viglione, Alberto; Castellarin, Attilio; Crisci, Massimiliano; Di Baldassarre, Giuliano
ABSTRACT: This work aims to provide a dynamic assessment of flood risk and community resilience by explicitly accounting for variable human behaviour, e.g. risk-taking and awareness-raising attitudes. We consider two different types of socio-hydrological systems: green systems, whereby societies deal with risk only via non-structural measures, and technological systems, whereby risk is dealt with also by structural measures, such as levees. A stylized model of human–flood interactions is first compared to real-world data collected at two test sites (People's Republic of Bangladesh and the city of Rome, Italy) and then used to explore plausible trajectories of flood risk. The results show that flood risk in technological systems tends to be significantly lower than in green systems. However, technological systems may undergo catastrophic events, which lead to much higher losses. Furthermore, green systems prove to be more resilient than technological ones, which makes them more capable of withstanding environmental and social changes.EDITOR D. Koutsoyiannis ASSOCIATE EDITOR not assigned